Prognostic model and immunotherapy prediction based on molecular chaperone-related lncRNAs in lung adenocarcinoma - Xu, Yue; Tao, Tao; Li, Shi; Tan, Shuzhen; Liu, Haiyan; Zhu, Xiao (Frontiers in Genetics, 2022)
Introduction: Molecular chaperones have been confirmed to be closely related to the occurrence and development of tumors, especially lung cancer. Our study aimed to construct a kind of molecular chaperone-related long non-coding RNAs marker to accurately predict the prognosis of lung adenocarcinoma patients and find new immunotherapy targets. Methods: In this study, we acquire molecular chaperone genes from two databases, Genecards and molecular signatures database. And then, we download transcriptome data, clinical data, and mutation information of LUAD patients through the Cancer Genome Atlas. MCRLncs were determined by Spearman correlation analysis. We use univariate, least absolute shrinkage and selection operator and multivariate Cox regression analysis to construct risk models. Kaplan-meier analysis was used to understand the difference in survival between high and low-risk groups. Nomogram, calibration curve, concordance index curve, and receiver operating characteristic curve were used to evaluate the accuracy of the risk model prediction. In addition, we use gene ontology enrichment analysis and kyoto encyclopedia of genes and genomes enrichment analyses to explore the potential biological functions of MCRLncs. Immune microenvironmental landscapes were constructed by using single-sample gene set enrichment analysis, tumor immune dysfunction and exclusion algorithm, “pRRophetic” R package, and “IMvigor210” dataset. The stem cell index based on mRNAsi expression was used to further evaluate the patient's prognosis. Results: Twenty MCRLncs were identified as independent prognostic indicators in patients with LUAD. Patients in the high-risk group had significantly worse overall survival. ROC curve suggested that the prognostic features of MCRLncs had a good predictive ability for OS. Immune system activation was more pronounced in the high-risk group. Prognostic features of the high-risk group were strongly associated with exclusion and cancer-associated fibroblasts. According to this prognostic model, a total of 15 potential chemotherapeutic agents were screened for the treatment of LUAD. Immunotherapy analysis showed that the selected chemotherapeutic drugs had potential application value. Stem cell index mRNAsi correlates with prognosis in patients with LUAD. Conclusion: Our study establishes a kind of novel MCRLncs marker that can effectively predict OS in LUAD patients and provides a new model for the application of immunotherapy in clinical practice.